I = ∫ 1 1 6 x ( x + 4 ) ln ( x ) d x
If I can be expressed as A ln ( A ) tan − 1 ( C B ) where A , B , C are positive integers with g cd ( B , C ) = 1 and A is a prime number. Then find the value of A + B + C .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good approach of using multiple change of variables to simplify the integral further. How does one come up with 2 tan y = t as the substitution to remove the denominator?
beautiful solution
I think you meant ln ( 2 cot ( y ) ) in the first line of the second paragraph.
Response to Challenge Master note : When ever we have x 2 + a 2 in the denominator, the best approach is by putting x = a tan ( t ) .
how does a baby learn his first steps or how does one realise that it is with our mouth that we must eat. literally it is the first substitution they make you learn in calculus class.
Problem Loading...
Note Loading...
Set Loading...
We have I = ∫ 1 1 6 x ( x + 4 ) ln ( x ) d x Make a substitution t = x We get I = 2 ∫ 1 4 t 2 + 4 2 ln ( t ) d x Make a substitution 2 tan ( y ) = t We get I = 2 ∫ arctan ( 1 / 2 ) arctan ( 2 ) ln ( 2 tan ( y ) ) d y 1 Now we will use properties of Definite Integrals (Property 3 from Basic Properties of Integrals )
We get
I = 2 ∫ arctan ( 1 / 2 ) arctan ( 2 ) ln ( 2 cot ( y ) ) d y 2 Adding 1 and 2 we get I = ∫ arctan ( 1 / 2 ) arctan ( 2 ) ln ( 4 ) d y I = 2 ln ( 2 ) arctan ( 3 / 4 )